Periosteum and fascia lata: Are they so different? - Manon, Julie; Evrard, Robin; Maistriaux, Louis; Fievé, Lies; Heller, Ugo; Magnin, Delphine; Boisson, Jean; Kadlub, Natacha; Schubert, Thomas; Lengelé, Benoît; Behets, Catherine; Cornu, Olivier (Frontiers in Bioengineering and Biotechnology, 2022)
Introduction Human fascia lata (HFL) has been largely used in reconstructive surgery in indications other than fracture repair. The goal of this study was to compare microscopic, molecular, and mechanical properties of HFL and periosteum (HP) in a bone tissue engineering perspective. Material & Methods Cadaveric HP and HFL (N=4 each) microscopic morphology was characterized using histology and immunohistochemistry (IHC), and the extracellular matrix (ECM) ultrastructure assessed by means of scanning electron microscopy (S.E.M.). DNA, collagen, elastin, glycosaminoglycans, major histocompatibility complex Type 1, and bone morphogenetic protein (BMP) contents were quantified. HP (N=6) and HFL (N=11) were submitted to stretch tests. Results Histology and IHC highlighted similarities (Type I collagen fibers; two-layer organization) but also differences (fiber thickness and compaction; cell type) between both tissues, as confirmed using S.E.M. The collagen content was statistically higher in HFL than HP (735 vs. 160.2µg/mg dry weight, respectively, p <0.0001). On the contrary, DNA content was lower in HFL than HP (404.75 vs. 1102.2µg/mg dry weight, respectively, p=0.0032), as was the immunogenic potential (p=0.0033). BMP-2 and BMP-7 contents did not differ between both tissues (p=0.132 and p=0.699, respectively). HFL supported a significantly higher tension stress than HP. Conclusion HP and HFL display morphological differences despite similar molecular ECM components. HFL stronger stretching resistance can specifically be explained by its higher collagen content. However, HFL contains much fewer cells and is less immunogenic than HP, the latter being rich in periosteal stem cells. In conclusion, HFL is likely suitable to replace HP architecture in order to confer a guide for bone consolidation, yet with absence of osteogenicity. This study could pave the way towards a bio-engineered periosteum built from HFL.